1989
DOI: 10.1007/bf00270245
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of interleukin-1 in human synovial fluid: detection by RIA, bioassay and presence of bioassay-inhibiting factors

Abstract: Synovial fluid (SF) from patients with osteoarthritis (OA), rheumatoid arthritis (RA), and various other arthridites was analyzed to assess the prevalence of interleukin-1 (IL-1) using both radioimmunoassay competitive inhibition specific for the beta form of IL-1 and the D10.G4.1 cell line bioassay which measures both alpha and beta forms of IL-1. Using radioimmunoassay competitive inhibition, IL-1 beta was found in 45% and 60% of individual samples from patients with OA and RA respectively. When RA and OA SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…Numerous investigators have reported finding IL-1 in synovial fluid specimens from many arthropathies, including OA (14 -16), and the range of the IL-1 levels seen in OA patients was similar to that seen in rheumatoid arthritis (RA) patients. In our study, IL-1␤ was present in 54% of OA synovial fluids and 41% of RA synovial fluids (16). A similar study from our laboratory documented the presence of macrophage-colony-stimulating factor (M-CSF) in OA synovial fluids (17).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Numerous investigators have reported finding IL-1 in synovial fluid specimens from many arthropathies, including OA (14 -16), and the range of the IL-1 levels seen in OA patients was similar to that seen in rheumatoid arthritis (RA) patients. In our study, IL-1␤ was present in 54% of OA synovial fluids and 41% of RA synovial fluids (16). A similar study from our laboratory documented the presence of macrophage-colony-stimulating factor (M-CSF) in OA synovial fluids (17).…”
Section: Introductionmentioning
confidence: 58%
“…To examine OA-associated inflammation earlier in the disease process, we studied synovial fluids collected by arthrocentesis. Earlier work from our laboratory found both IL-1␤ and M-CSF in OA synovial fluids (16,17). Here we assayed for TNF-␣, an important mediator of inflammation in rheumatoid synovium, and IL-6, a cytokine whose levels in knee synovial fluids has been correlated with inflammatory infiltrates (26).…”
Section: Oa Synovial Fluid Contains Markers Of Inflammationmentioning
confidence: 97%
“…The mediator is a potent stimulator of proteoglycan degradation and an inhibitor of proteoglycan synthesis in cartilage explants, leading to rapid net depletion of this matrix molecule (35)(36)(37). In addition, IL1 has been detected in the synovial fluid from patients with OA (38)(39)(40). IL1 mRNA has also been demonstrated in isolated human articular chondrocytes from one individual (41) and in cultured rabbit chondrocytes (42).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, one of the main factors which stimulate collagenase and PGE, production by mesenchymal cells such as joint synovial fibroblasts (Dayer et al, 1986), is known to be prestnt in rheumatoid synovial fluid (Smith et a]., 1989;di Giovini: and Duff, 1990;Rooney et al, 1990;Westacott et al, 1990;Fong et al, 1994), but precise assay has been hampered by interfering components in synovial fluid.…”
Section: Discussionmentioning
confidence: 99%